Low threshold linear cavity mode-locked fiber laser using microfiber-based carbon nanotube saturable absorber - Lau, K.Y.; Ng, E.K.; Abu Bakar, M.H.; Abas, A.F.; Alresheedi, M.T.; Yusoff, Z.; Mahdi, M.A. (Elsevier, 2018)
In this work, we demonstrate a linear cavity mode-locked erbium-doped fiber laser in C-band wavelength region. The passive mode-locking is achieved using a microfiber-based carbon nanotube saturable absorber. The carbon nanotube saturable absorber has low saturation fluence of 0.98 µJ/cm2. Together with the linear cavity architecture, the fiber laser starts to produce soliton pulses at low pump power of 22.6 mW. The proposed fiber laser generates fundamental soliton pulses with a center wavelength, pulse width, and repetition rate of 1557.1 nm, 820 fs, and 5.41 MHz, respectively. This mode-locked laser scheme presents a viable option in the development of low threshold ultrashort pulse system for deployment as a seed laser.